SARS-CoV-2 transmissions in students and teachers: seroprevalence follow-up study in a German secondary school in November and December 2020 - Reinhard Berner; Jakob Peter Armann; Carolin Kirsten; Lukas Galow; Elisabeth Kahre; Luise Haag; Alexander Dalpke; Christian Lück (BMJ Publishing Group, 2021)
Objective To quantify the number of undetected SARS-CoV-2 infections in educational settings.Design Serial SARS-CoV-2 seroprevalence study before and during the second wave of the COVID-19 pandemic.Setting Secondary school in Dresden, Germany.Participants Grade 8-12 students and their teachers were invited to participate in serial blood sampling and SARS-CoV-2 IgG antibody assessment.Main outcome measure Seroprevalence of SARS-CoV-2 antibodies in study population.Results 247 students and 55 teachers participated in the initial study visit and 197 students and 40 teachers completed follow-up. Seroprevalence increased from 1.7% (0.3-3.3) to 6.8% (3.8-10.1) during the study period mirroring the increase of officially reported SARS-CoV-2 infections during this time. The ratio of undetected to detected SARS-CoV-2 infections ranged from 0.25 to 0.33.Conclusions We could not find evidence of relevant silent, asymptomatic spread of SARS-CoV-2 in schools neither in a low prevalence setting nor during the second wave of the pandemic, making it unlikely that educational settings play a crucial role in driving the SARS-CoV-2 pandemic.Trial registration number DRKS00022455.